Non‐native English teachers' confidence in their own pronunciation and attitudes towards teaching: A questionnaire survey in Japan. (13th March 2019) - Uchida, Yoko; Sugimoto, Junko
Abstract : The purpose of this study is to investigate non‐native English teachers' attitudes towards pronunciation instruction by exploring their pronunciation model and goal preferences and confidence in their own pronunciation. The questionnaire survey data of 100 public junior high school teachers in Tokyo indicated that the majority were less confident in pronouncing sentences and passages than words, while overseas experience had a positive effect on confidence. Covariance structure analysis confirmed that confidence led to positive attitudes towards pronunciation instruction. Native varieties were preferred as models and goals, despite a changing global context in which World Englishes are increasingly important. We discuss the necessity of providing teacher training that incorporates areas in which teachers feel less confident and setting the pronunciation goal of "intelligible pronunciation." Abstract : 本研究の⽬的は、⾮⺟語話者の英語教員が好む発⾳のモデル及び設定する到達⽬標、⾃⾝の発⾳に対する⾃信の有無が、発⾳指導に対する態度にどのような影響を与えるかを探ることである。東京の公⽴中学校教員100名に対しておこなったアンケート調査から、教員の⼤多数は語と⽐べると⽂やパッセージの発⾳に⾃信を有していないこと、海外経験が発⾳に対する⾃信に良い影響をもたらしていることなどがわかった。また、共分散構造分析により、⾃⾝の発⾳に対して⾃信を有していることが発⾳指導への前向きな態度につながることが明らかとなった。世界で多様な英語変種が使われているにもかかわらず、発⾳のモデルや到達⽬標は⺟語話者の英語変種を選ぶ傾向が確認された。教員⾃⾝の発⾳の到達⽬標を「明瞭度の⾼い発⾳」に設定するとともに、教員が⾃信を⽋いている領域を中⼼とした発⾳訓練の必要性について論じる。